2019
DOI: 10.3389/fneur.2019.01126
|View full text |Cite
|
Sign up to set email alerts
|

Underlying Small Vessel Disease Associated With Mixed Cerebral Microbleeds

Abstract: Background and Purpose: Whether patients with both lobar and deep cerebral microbleeds (mixed CMB) have advanced cerebral amyloid angiopathy (CAA), hypertensive angiopathy (HA) or both is uncertain. To get insight into the underlying small vessel disease (SVD) associated with mixed CMB, we explored its association with cortical superficial siderosis (cSS), a key marker of CAA and other MRI markers of SVD in patients with intracerebral hemorrhage (ICH).Methods: Of 425 consecutive patients with acute ICH who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…48 Similarly, we found a relatively high prevalence of mixed cerebral microbleeds in patients with ICH irrespective of location, which may reflect the presence of etiologies other than or in addition to CAA. 49,50 Our observation that the prevalence of cortical superficial siderosis was much higher in patients with ICH or lobar ICH compared to the general population, cognitively normal individuals, and patients with AD, indicates that cortical superficial siderosis is not a marker for CAA in general, but may be confined to specific clinical phenotypes 37 and related with the development of lobar ICH. 51…”
Section: Caa In Patients With (Lobar) Ichmentioning
confidence: 89%
“…48 Similarly, we found a relatively high prevalence of mixed cerebral microbleeds in patients with ICH irrespective of location, which may reflect the presence of etiologies other than or in addition to CAA. 49,50 Our observation that the prevalence of cortical superficial siderosis was much higher in patients with ICH or lobar ICH compared to the general population, cognitively normal individuals, and patients with AD, indicates that cortical superficial siderosis is not a marker for CAA in general, but may be confined to specific clinical phenotypes 37 and related with the development of lobar ICH. 51…”
Section: Caa In Patients With (Lobar) Ichmentioning
confidence: 89%
“…Third, the number of patients is considerably smaller compared to the above mentioned studies maybe mitigating a possible difference between the groups. Studies on patients with CAA and mixed CMB and macrohaemorrhages in European [ 20 ] and Asian [ 21 ] populations found that CMB is mainly driven by hypertensive vasculopathy although a subgroup of these patients might have coexisting or dominant CAA. Further studies on the natural history of mixed CMB should shed more light on the early stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…115 The association between CMB presence (≥1) and symptomatic ICH failed to reach statistical significance (adjusted OR (aOR) =1. 42 115 Interestingly, a recent study using a multistep algorithm populated with data from clinical studies to estimate 3-month clinical and imaging outcomes in patients with acute IS with high CMB burden (>10 CMBs) treated with IVT reported the following findings: (A) the beneficial treatment effect of IVT on 3-month functional outcome was attenuated in patients with >10 CMBs compared with patients with ≤10 CMBs on pretreatment brain MRI; (B) IVT was related to an increased risk of mortality in patients with >10 CMBs; (C) IVT might be related to net harm in subgroups of patients with >10 CMBs defined by age, stroke symptom severity and treatment delay; nevertheless, (d) Routine pretreatment MRI to quantify CMB burden before IVT cannot generally be recommended, as long as it causes even a small additional treatment delay given the low general pretest probability of >10 CMBs (0.6%-2.7%). 116 However, these inferences derived from observational data need to be treated cautiously.…”
Section: Reperfusion Therapies For Acute Is and Cmbsmentioning
confidence: 99%